Taking memory by force. A review of «Los dos demonios (recargados)» (The two demons (reloaded), by Daniel Feierstein. Buenos Aires: MAREA, 2018, 272 p - Toledo Bugarini, Diego Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The work reviewed here offers an exploration and characterization around the theory of the demons and its present “reloaded” version. The theory was presented in the Prologue of the text Nunca Más (Never again), elaborated by the National  Commission for the Disappearance of People (CONADEP, by its acronym in Spanish) in 1984, and became very important during the 80s  as a central element for the social recomposition of the return of democracy, and started to be questioned as from the 90s. With it, the state and insurgent violence were equated in their responsibilities for unleashing terror, presenting the society as a victim of this abstract and depoliticising violence.   Through its multiple paths, this work offers the opportunity to reformulate the analysis about the relationship between these types of violence in other scenarios of the region in order to think, especially, about the dictatorial processes of the second half of the 20th century and the consequences suffered in the present regarding the different ways in which the collective memory about political repression in the region was constructed. In this sense, the author dissects the reloaded version of the theory and shows how denial and the demonization of the past were revisited in order to stigmatise actors of the present, relegitimise the repressive violence of the state and the advancement of regressive social and economic policies that are currently deployed in the Argentinian territory.